Optimalisasi Kompetensi Tenaga Kerja Muda melalui Pelatihan Microsoft Office dan Sistem Administrasi Digital untuk Meningkatkan Peluang Kerja - Dian Purnama Sari; Muhammad Syahrizal; Wardayani Wardayani; Ahmad Harun Daulay; Syamsul Bahri (JPM: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve the competencies of young workers through Microsoft Office and digital administration training to support work readiness in Medan City. The main problem faced by the participants was the low ability to use digital office applications, particularly Microsoft Word, Microsoft Excel, and Microsoft PowerPoint, which are essential skills in the modern workplace. The implementation methods included observation, practice-based training, mentoring, evaluation, and follow-up activities. The participants consisted of 20 young workers with senior high school and vocational school educational backgrounds. Initial survey results showed that 60% of participants were in the low competency category, 30% in the moderate category, and only 10% in the high category. After the training activities were conducted, participant competencies increased significantly, with the high competency category rising to 55%, the moderate category reaching 35%, and the low category decreasing to 10%. In addition to improving technical digital administration skills, the program also had a positive impact on participants’ confidence in facing technology-based employment opportunities. The partners’ responses indicated a high level of satisfaction because the training materials were considered relevant to current community and labor market needs. Therefore, this community service program can serve as an effective solution for improving the digital competencies of young workers and supporting the enhancement of human resource quality in the era of digital transformation.